Light‐Induced Ammonia Generation over Defective Carbon Nitride Modified with Pyrite (Adv. Energy Mater. 43/2022). Issue 43 (17th November 2022) - Zander, Judith; Timm, Jana; Weiss, Morten; Marschall, Roland
Abstract : Ammonia Generation In article number 2202403, Roland Marschall and co‐workers utilize two earth‐abundant materials, namely defective polyheptazine and pyrite, in combination to generate ammonia under light irradiation. Generating ammonia decentralized by photocatalysis is a promising approach and sustainable alternative to Haber‐Bosch.